loose Seton in management of high anal fistula. - Sagban, Nabeel J. (Journal of the Faculty of Medicine Baghdad, 2015)
Background: The treatment of high anal fistulae needs to meet a balance of cure and continence. There are many surgical treatment options available for high fistula-in-ano. The best surgical operation for high anal fistulas is difficult to define because they have varying cure and incontinence rates. A loose Seton is a loop of flexible material (silastic tube, silk, and nylon) placed through the fistulous track to allow drainage by keeping the external skin opening patent. Some surgeons use the loose Seton to allow drainage and others believe that it promotes healing by inducing fibrosisObjective: To check the efficacy of loose Seton in the management of high anal fistulas.Patient and method: A prospective study of 26 patients with high anal fistula managed by loose Seton placement between February- 2009 and February-2010 in 3rd surgical unit, fifth floor, Baghdad teaching Hospital The seton is removed after 3 months in outpatient clinic, follow up for 6 months.Results: Out of 26 patients, 23 were males and 3 were females, the male to female ratio was 7.7:1. Peak occurrence was noted between 30 to 40 years. Minor incontinence was noted in two patients, those patients lost control of flatus which persisted for 4 months. No fecal incontinence noticed in any patient. .In 21 patient the fistulas were successfully eliminated (Success rate =81%) by loose Seton treatment alone, while fistula recurs in five patients (Failure rate =19%).Conclusion: The use of one stage loose Seton is safe and effective in the treatment of high anal fistula.